Determinants of fast marathon performance: low basal sympathetic drive, enhanced postcompetition vasodilatation and preserved cardiac performance after competition. Issue 11 (18th January 2008) - Gratze, G; Mayer, H; Luft, F C; Skrabal, F
Abstract : Objective: To test the hypothesis that enhanced postexercise vasodilatation is related to sympathetic drive to resistance vessels and to fast marathon performance. Design: Prospective field study before and after running a marathon. Participants: 51 healthy amateur runners who volunteered to participate. The fastest competitor finished fourth, the slowest 1290th out of 1324 participants. Interventions: None. Main outcome measurements: Competition time, beat-to-beat blood pressure by the vascular unloading technique, oscillometric blood pressure, beat-to-beat stroke volume by impedance cardiography, total peripheral resistance changes calculated from blood pressure and stroke volume changes, sympathetic modulation of vasomotor tone and parasympathetic modulation of sinus node function by spectral analysis of blood pressure and heart rate variability, baroreceptor reflex sensitivity by the sequence method. Results: Slow performers, in contrast to fast performers, exhibited a higher 0.1 Hz band of diastolic blood pressure variability before the competition (0.1 Hz BPV) (40.0 (SD 2.39) vs 54.9 (2.47), p<0.001), diminished vasodilatation (−11.3 (4.78) vs −29.4 (3.23), p<0.01) and a decrease in stroke index (−14.9 (3.55) vs +0.9 (3.37), p<0.001) in response to the race. Single and multiple regression analyses further corroborated the findings. Conclusions: Fast performance in the marathon is associated with low sympathetic modulation of vasomotor tone, maintained stroke index postcompetition and enhanced exercise-induced vasodilatation. We postulate that maintaining a low level of sympathetic modulation to resistance vessels during the course of training may indicate its appropriateness, thus enabling fast performance by optimal postexercise vasodilatation and by prevention of postcompetition cardiac dysfunction. This will have to be tested in future longitudinal studies.